2004
DOI: 10.1142/s0192415x04002478
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Tetrandrine on Pulmonary Metastases in CT26 Colorectal Adenocarcinoma–Bearing BALB/c Mice

Abstract: Tumor metastasis is a major cause of mortality in cancer patients. The anti-metastatic effect of tetrandrine, an alkaloid isolated from Stephania tetrandrae S. Moore, was investigated in a pulmonary metastatic model of colorectal cancer-bearing mice. Tetrandrine decreased the viability of murine colorectal adenocarcinoma CT26 cells in a time- and dose-dependent manner. CT26 cells were injected into BALB/c mice via a tail vein to establish pulmonary metastases. After this, the mice were given intraperitoneal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…metastases, compared with vehicle-treated mice, and no acute toxicity or marked changes in body weight were observed (25). The results of the present study indicated that the EGF-induced invasion of HT29 cells was suppressed by tetrandrine through the inactivation of EGFR and downstream molecules, including suppression of the phosphorylation cascade of PI3K, PDK1 and AKT, and the reduction of p-ERK, which was in agreement with a previous study on lung cancer cells (44).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…metastases, compared with vehicle-treated mice, and no acute toxicity or marked changes in body weight were observed (25). The results of the present study indicated that the EGF-induced invasion of HT29 cells was suppressed by tetrandrine through the inactivation of EGFR and downstream molecules, including suppression of the phosphorylation cascade of PI3K, PDK1 and AKT, and the reduction of p-ERK, which was in agreement with a previous study on lung cancer cells (44).…”
Section: Discussionsupporting
confidence: 92%
“…It has been shown that tumor cell apoptosis caused by tetrandrine exhibits inhibitory effects on various types of tumor cell (24)(25)(26)(27)(28)(29). The results of the present study indicated that tetrandrine had no cytotoxic effect on the HT29 cells, however, the anti-metastatic effect of tetrandrine on EGF-induced HT29 cancer cells was observed, and the underlying molecular signaling was evaluated.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…12 Another report demonstrated that intraperitoneal injection of 10 mg/kg/day tetrandrine for 5 days (starting from the day of intravenous injection of tumor cells) reduced the number of pulmonary metastatic foci of colon cancers by 40%. 35 However, tumor model used in the colon cancer study represents small tumor model because tumors were treated immediately after injection of tumor cells. In our study, we increased the dose of tetrandrine to 150 mg/kg/day and started treatment either immediately or 5 days after tumor cell inoculation.…”
Section: Discussionmentioning
confidence: 99%